(untitled) (Fiep Bulletin - online, 2015)
INTRODUCTION: The present study aimed to analyze the process of football training base category of a professional Club and a football school in the under 13 category both in Rio de Janeiro, as well as the coaches interviewed. MATERIAL AND METHODS: The study was characterized by a descriptive research. The technique of observation used was the systematic and direct of the trainings with the use of a video camera and subsequent transcription of data into observation sheets, as well as a questionnaire used as data collection instrument, applied to 30 football coaches being coaches 9 basic categories and 21 coaches football school. The scheme adopted was adapted and similar to procedures used in the study of Saad (2002) to include the detailed analysis of the exercises performed. The results of the questionnaires indicate that the coaches evaluated seem to possess the training and experience necessary to carry out its function, but do not apply their theoretical and practical knowledge in their workouts. RESULTS: The result of the analysis of the observation of Youth Team and training of the football school confirmed some similarities in the segments, mainly in the game itself, where teams occupy most of the full time. Other similarities between the two teams were in the game I complex exercises, where both teams did not use a logical progression, showing little concern with the systematic repetition of the tactical-technical situations for acquisition of staff behaviour patterns. CONCLUSION: Clear the largest recovery by results and greater concern about the performance of the team in both situations, contributing to an early specialization of the athlete and can cause problems in physical, cognitive, affective and social development of the child. When analyzing the data from the observation of training, it is important to consider the different goals of each team. The base category aims at acquiring the physical, technical and tactical aspects by parties, leading athletes to total income. Aims at training school and of the citizen, through diverse activities, which develop all through sports. The results obtained reveal important facts about the methodologies of teaching and training of the sport of football.